1985
DOI: 10.3109/00365528509088848
|View full text |Cite
|
Sign up to set email alerts
|

Food Intake before and after Gastroplasty for Morbid Obesity

Abstract: Preoperatively, the energy intake was high, the protein intake was sufficient, whereas the relative contribution of fat was greater than and of carbohydrate less than the recommended values. After gastroplasty a dramatic fall occurred in the intake of energy and all nutrients, and a relative reduction in the contribution of fat at 3 months and of carbohydrate at 12 months was observed. Preoperatively, the intake of vitamins D, B6, folacin, biotin, magnesium, iron, zinc, manganese, copper, and fluoride was defi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
4

Year Published

1994
1994
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 9 publications
1
9
0
4
Order By: Relevance
“…Our ®nding of mean dietary iron intakes below RDI throughout the study is consistent with the results of several other authors who have reported mean iron intakes below RDI in both the early postoperative period 3,4,6 (where reduced levels of micronutrient carrier proteins may contribute) and the late 5,6 postoperative period. Mean zinc intake was`50% RDI at 12 months.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Our ®nding of mean dietary iron intakes below RDI throughout the study is consistent with the results of several other authors who have reported mean iron intakes below RDI in both the early postoperative period 3,4,6 (where reduced levels of micronutrient carrier proteins may contribute) and the late 5,6 postoperative period. Mean zinc intake was`50% RDI at 12 months.…”
Section: Discussionsupporting
confidence: 81%
“…While it is not surprising that short-term studies have shown that the intakes of many nutrients are below the recommended dietary intake (RDI) in the early postoperative period, 3,4 it is of concern that several small long-term studies indicate that the intake of a number of important nutrients may remain below the RDI at 1±2 years postoperatively. 5,6 It is, however, unclear from these studies what level of dietary advice, if any, was given to subjects preoperatively or at follow-up. Nutritional supplementation is increasingly being advised for all patients who undergo gastric restrictive surgery, 4,6,7 but details of compliance are often not recorded or reported.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although effective as a weight loss procedure, concern has been raised regarding the possibility that gastroplasty may have a nutritional cost (6,7,25,26), particularly in the early postoperative phase when body weight loss is typically the most drastic (13). Recent interest has focused on the relationship between elevated circulating homocysteine concentrations and atherosclerotic and thrombotic vascular diseases (8).…”
Section: Discussionmentioning
confidence: 99%
“…Caloric intake often increases significantly during the postoperative course. 8,[14][15][16][17][18][19] In the Swedish Obese Subjects trial, 8 surgery patients consumed approximately 2900 kcal/ d prior to surgery. Their intake decreased to approximately 1500 kcal/d 6 months after surgery, but increased to approximately 2000 kcal/d 10 years later, when patients had regained approximately 10% of their maximum weight loss.…”
Section: Introductionmentioning
confidence: 99%